Agri-Business Curriculum: The Entrepreneurial Direction of Graduates - Patagoc, Regie D. (Open Science Journal, 2019)
This study aimed to determine the entrepreneurial engagement of Agri-Business graduates from Southern Philippines Agri-Business and Marine and Aquatic School of Technology (SPAMAST), during the SY 2008-2013. The data was collected using a self-administered questionnaire, analyzed and subjected to the measures of central tendency (mean and percentage) and the Statistical Package for Social Sciences (SPSS 19.0). Results showed that graduates were within 26 to 30 years old age, female, single, most were regular workers in a private company with 1 - 3 years working experience and were practicing entrepreneurs earning a monthly income of 10,000. High rating was extended to the level of competence on attitudinal, behavioral and educational factors. It was found out that, the respondents either felt, thought and view entrepreneurship as a thing that they had dreamed to undertake after graduation because they believed that it is only doing entrepreneurial undertakings that they can fulfill the objectives of the course and their personal beliefs that success can be attained through it. Further, only few graduates had started their entrepreneurial engagement, while the majority, were still thinking about their entrepreneurial endeavor because of the difficulty in starting own business due to the complex administrative procedures involved. The demographic and socio-economic profile had no significant influence to the level of engagement while the level of competencies significantly influenced the level of entrepreneurial engagement.